NILs of Cold Tolerant Japonica Cultivar Exhibited New QTLs for Mineral Elements in Rice - Ali, Muhammad Kazim; Sun, Zheng-Hai; Yang, Xiao-Meng; Pu, Xiao-Ying; Duan, Cheng-Li; Li, Xia; Wang, Lu-Xiang; Yang, Jia-Zhen; Zeng, Ya-Wen (Frontiers in Genetics, 2021)
Chilling stress at booting stage can cause floret deterioration and sterility by limiting the supply of food chain and the accumulation of essential mineral elements resulting in reduction of yield and grain quality attributes in rice. Genomic selection of chilling tolerant rice with reference to the accumulation of mineral elements will have great potential to cope with malnutrition and food security in times of climate change. Therefore, a study was conducted to explore the genomic determinants of cold tolerance and mineral elements content in near-isogenic lines (NILs) of japonica rice subjected to chilling stress at flowering stage. Detailed morphological analysis followed by quantitative analysis of 17 mineral elements revealed that the content of phosphorus (P, 3253 mg/kg) and potassium (K, 2485 mg/kg) were highest while strontium (Sr, 0.26 mg/kg) and boron (B, 0.34 mg/kg) were lowest among the mineral elements. The correlation analysis revealed extremely positive correlation of phosphorus (P) and copper (Cu) with most of the cold tolerance traits. Among all the effective ear and the second leaf length correlation was significant with half of the mineral elements. As a result of comparative analysis, some QTLs (qBRCC-1, qBRCIC-2, qBRZC-6, qBRCHC-6, qBRMC-6, qBRCIC-6a, qBRCIC-6b, qBRCHC-6 and qBRMC-6) identified for calcium (Ca), zinc (Zn), chromium (Cr) and magnesium (Mg) on chromosome number 1, 2 and 6 while, a novel QTL (qBCPC-1) was identified on chromosome number 1 for P element only. These findings provided bases for the identification of candidate genes involved in mineral accumulation and cold tolerance in rice at booting stage.